Effect of Preferred Volume Setting on Speech Audibility in Different Hearing Aid Circuits - Souza, Pamela E.; Kitch, Virginia J. (Journal of the American Academy of Audiology, 2001)
This study compared preferred volume setting for linear peak clipping, compression limiting, and wide dynamic range compression (WDRC) amplification and quantified speech audibility at the preferred volume setting for each amplification type. Ten listeners with mild-to-moderate hearing loss were fitted monaurally with a behind-the-ear hearing aid programmed sequentially with WDRC, compression limiting, and linear peak clipping amplification. Speech was presented in quiet and in noise at a range of input levels. In each condition, the listener adjusted the volume for maximum clarity. Signal levels were measured using a probe microphone system. There was no significant difference in speech audibility between amplification strategies for any speech level regardless of the presence or absence of background noise. These results imply that the improved audibility advantage of WDRC over linear amplification demonstrated in controlled environments may not be maintained in situations where the hearing aid wearer controls the volume.Abbreviations: AAI = Aided Audibility Index, AI = Articulation Index, ANOVA = analysis of variance, NAL-R = National Acoustic Laboratories-Revised, SIR = Speech Intelligibility Rating, WDRC = wide dynamic range compression
Keywords: Amplification; audibility; clarity; preferred volume